Political theology and law - Preterossi, Geminello (Law and Politics Ser., 2022)
Cover -- Half Title -- Series -- Title -- Copyright -- Dedication -- Table of Contents -- Introduction: can we do without political theology? -- 1 The mortal god -- 2 The "political" as the power of the negative -- 3 The worldly god -- 4 Politics as a "religious question -- 5 Political theology and populism -- 6 Critique of economic theology -- Conclusions: the sense of what is missing -- Index.